2020
DOI: 10.5114/aoms.2020.97764
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between endocan and obstructive sleep apnea severity

Abstract: Introduction: Obstructive sleep apnea (OSA) and endothelial dysfunction are associated with cardiovascular risk factors and the development of atherosclerosis. Endocan is a marker of endothelial dysfunction, while obstructive sleep apnea is one of the causes of endothelial dysfunction. In this study, we investigated the relationship between endocan and obstructive sleep apnea severity. Material and methods: A total of 179 patients with snoring complaints were included. All patients underwent polysomnography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Among these 28 studies, 16 were excluded; the reasons for exclusion are listed in Figure 1. Ultimately, 12 studies [17,18,[25][26][27][28][29][30][31][32][33][34] were included in the meta-analysis.…”
Section: Study Inclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these 28 studies, 16 were excluded; the reasons for exclusion are listed in Figure 1. Ultimately, 12 studies [17,18,[25][26][27][28][29][30][31][32][33][34] were included in the meta-analysis.…”
Section: Study Inclusionmentioning
confidence: 99%
“…Six studies [17,25,26,28,31,32] addressed the association between endocan levels and AHI, FMD, minimal O 2 saturation, CIMT, and BMI. Moreover, 5 studies [18,[25][26][27][28] reported serum endocan levels as an independent risk factor for OSAHS. All studies had NOS scores ≥ 5.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous positive airway pressure (CPAP) is recognized as the most effective therapy for patients suffering from OSAHS [ 6 ]. However, it still needs to be clarified whether CPAP is effective in treating hypertension in patients suffering from OSAHS.…”
mentioning
confidence: 99%